ASSISTANCE IN LEARNING THE UMMI METHOD FOR 6TH GRADE STUDENTS OF SDIT EL-HAQ SIDOARJO WHO ARE FALLING BEHIND - Eka Putri, Rahma; Ghozali, Solchan (PT. Antis International Publisher, 2025)
Objective: This study evaluated the effectiveness of a mentoring program aimed at enhancing mastery of the Ummi method in Qur'anic recitation among underperforming 6th grade students at SDIT El-Haq Sidoarjo. Method: The intervention combined intensive consultation, talaqqi sessions, muroja'ah, and periodic evaluations, with data collected through observational assessments and structured feedback from educators and students. Results: The program significantly improved recitation fluency, comprehension, and learning motivation, effectively addressing identified learning deficiencies. Novelty: Integrating traditional recitation practices with modern mentoring techniques, this study offers a replicable model that underscores the importance of collaborative support between schools and parents in enhancing religious literacy.